Development of the circadian clockwork in the kidney - Mészáros, Krisztina; Prüß, Linda; Szabó, Attila J.; Gondan, Matthias; Ritz, Eberhard; Schaefer, Franz (Kidney international, 2014)
The circadian molecular clock is an internal time-keeping system composed of centrally synchronized tissue-level pacemakers. Here, we explored the ontogeny of the clock machinery in the developing kidney. Pregnant rats were housed at 12-12 h light-dark cycles. Offsprings were killed at 4-h intervals on embryonic day 20 and at postnatal weeks 1, 4, and 12. Canonical clock gene (Clock, Bmal1, Rev-erbα, Cry1, Cry2, Per1, Per2) and kidney-specific clock-controlled gene (αENaC, SGK1, NHE3, AVPR2) expression was profiled by RT-PCR. To investigate the role of nutritional cues, the feeding pattern was modified postpartum. Clock, Rev-erbα, Per2, αENaC, SGK1, NHE3, and AVPR2 showed circadian expression at the end of intrauterine development. By 1 week, all genes oscillated with a distinct acrophase shift toward the time of peak feeding activity. Daily 4-hour withdrawal of mothers induced a 12-hour phase shift of Clock and Bmal1 expression, while disrupting oscillations of the other genes. After weaning, oscillation phases shifted back toward the adult pattern, which was fully expressed at 12 weeks. Thus, functional circadian molecular clockwork evolves in the late fetal and early postnatal kidney. During the nursing period, oscillations are entrained by nutritional cues. The coupling of the circadian expression of tubular regulators of fluid and electrolyte excretion to the feeding-entrained clockwork may be important to maintain homeostasis during this critical period.